Analysis of spatial power synthesis efficiency based on the near-field cross-beam theory for distributed UAV interference applications - Xu, Dalong; Wu, Jian; Cao, Jianyin; Wang, Hao; Li, Xiang (Frontiers of information technology & electronic engineering, 2024)
This paper discusses a novel method for calculating near-field spatial power synthesis efficiency based on the cross-beam synthesis theory for the application of unmanned aerial vehicle (UAV) swarms in electronic countermeasure systems. The model of a UAV array and the working principle of the nearfield spatial power synthesis are used to explain the power synthesis efficiency of UAV interference. The influence of location parameters, such as the positioning and attitude accuracy of UAVs, is analyzed. The influences of UAVs in actual situations, including the jitter of platforms, damage rate, and time synchronization accuracy in real conditions, are also analyzed. Finally, a test scenario based on fiber-optic synchronization is constructed to measure the spatial power synthesis efficiency with high-precision time synchronization. The results provide further evidence of the effectiveness and reliability of the proposed near-field cross-beam calculation method for distributed UAV interference applications.